Empowering Teenagers from Rahpia Orphanage Through Making Gift Bouquets and Financial Report Training - Hantono Hantono; William Tjong; Asen Susanto; Teng Sauh Hwee (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
This community service activity aims to provide knowledge, develop creativity, especially in processing paper into beautiful handicrafts, attitudes, abilities (basic skills), imagination, and talent in combining beautiful colors, from the teenagers of the Rahpia Orphanage. This is done in the form of making a gift bouquet. The bouquet marketing process that has been completed and the knowledge of making financial reports in accordance with applicable standards are also taught. The methods used is socialization and training. This is expected to help solve the problems being faced by the caretakers of the Rahpia Orphanage.